Lebensstile und Wohnstandortwahl - Rössel, Jörg; Hölscher, Michael (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2012)
Life style research and various disciplines dealing with regional studies argue that life styles are explanatory relevant for decisions in different behavioral areas, in particular for residential choices. However, the results of previous research are rather mixed. To specify the conditions for the explanatory relevance of life style based preferences for locational choices, this article ties in with a parsimonious decision theoretic model, which has been applied both in the sociology of the city and in life style research. Based on this theoretical framework an empirical study is presented, which tests the explanatory relevance of life styles for residential choices. The study is based on neighborhood survey data from Leipzig, representing a context, in which a strong impact of life styles may be expected. However, even in this context the empirical study shows rather limited explanatory power of life style based preferences for residential choices, whereas household arrangements and economic resource endowments of persons show much more explanatory power.
Zusammenfassung unter dem Titel: Life styles and residential choice
Gesehen am 16.08.2018